Support in reporting and registration of Bosnian emigrants for the Embassy of Bosnia and Herzegovina in Prague - Josipović, Ivona (2021)
The main goal of this bachelor's thesis, which focuses on analyzing the needs and problems of the Embassy of Bosnia and Herzegovina in Prague, is to create an application for adding and editing records and building a dynamic dashboard according to the established needs. The main goal is to create a SW application for emigrant registration and reporting. In the theoretical part, the author explains the basic concepts of data visualization, dashboards, and its creation principles. This section also includes an introductory chapter on the Embassy of Bosnia and Herzegovina in Prague. The practical part defines the needs and criteria for creating a system and dashboard, determined by an interview with the staff of the Embassy of Bosnia and Herzegovina in Prague. The main benefit and result of this part will be a functional application and dashboard, created with the recommended principles from the thesis's theoretical part. In the last part, user testing verifies the application and dashboard functionality and whether users can easily utilize them.